THE COMPONENT CHARACTERISTICS OF A FAVORITE TEACHERIN THE ERA OF INDUSTRIAL REVOLUTION 4.0(Study in verses 129 and 151 of Surah al-Baqarah)مكونات شخصية المعلم المختارة في عصر الثورة الصناعية الرابعة (دراسة من خلال آيتي 921 و 151 من سورة البقرة) - Moh. Abdul Kholiq Hasan (Universitas Muhammadiyah Surakarta, 2022)
This research aims to investigate the components of chosen teachers’characteristics in the industrial revolution era 4.0 based on the cue of verse 129 and 151of surah al-Baqarah. It employed library research method with descriptive qualitativeapproach. Content analysis theory was used to analyze the texts of verse 129 and 151 ofsurah al-Baqarah and related commentaries with the contextualization approach of theQur’an. The results indicate that the components of chosen teachers’ characteristics inthe industrial revolution era 4.0 fit with the cue of verse 129 and 151 of surah al-Baqarahas follows: (1) Having extensive reading and consistent with al-Quran and scienceand technology related to industry 4.0, (2) Teaching al-Quran and writing, includingelectronic writing, (3) Teaching wisdom in the form of expertise in interacting withthe development of industrial technology 4.0, (4) Purifying the soul from all badnessincluding paying attention to practical ethics with industrial technology 4.0, (5) Continue.to increase knowledge of industrial technology 4.0